Production Practices, Postharvest Handling, and Quality of Cowpea Seed Used by Farmers in Makueni and Taita Taveta Counties in Kenya - Mary W. Njonjo; James W. Muthomi; Agnes W. Mwang’ombe (International Journal of Agronomy)
Over 80% of farmers in the developing countries use seeds from the informal seed supply that is of unknown quality status with low physical purity, reduced vigour, and contamination with seed-borne pathogens. A survey involving 114 farmers was conducted in Makueni and Taita counties using a semistructured questionnaire to determine cowpea production practices. Forty-seven cowpea seed samples were collected from farmers, and thirty-four were collected from markets and analysed for physical and physiological quality. The data from the questionnaire were analysed using SPSS package. Majority, over 76% of farmers used farm-saved seeds and intercropped cowpea with cereals (56%). The common storage container was polythene bags (56%), and farmers did not treat the seeds. The seed was below the recommended purity standard of 98%. In Taita, farm-saved and market-sourced seeds met the recommended 75% germination at 82.7% and 76.8%, respectively. Even though the germination standard was met, seeds were of low physical purity and reduced vigour. Farmers should be enlightened on recommended production practices, methods of harvesting, and postharvest handling practices to reduce seed quality loss during storage and maximize production.